2018
DOI: 10.4067/s0718-58392018000400539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brassinolide application on antioxidant characteristics and endogenous hormones of Leymus chinensis (Trin.) Tzvelev under different light intensity regimes

Abstract: Different light and shade intensities are the main constraints to achieve potential biomass accumulation in Leymus chinensis (Trin.) Tzvelev. An experiment was conducted to explain the physiochemical and morphological adversity triggered by various light intensities. Adverse impacts were lessened with exogenous brassinolide (BR). Treatments consisted of 100% natural light (T0), 100% natural light + 0.1 mg L-1 BR (BT0), light shade (70% natural light) (T1), light shade + BR (70% natural light + 0.1 mg L-1 BR) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Given that low light intensity can impact stress tolerance in various plants, such as Calamus viminalis, Anoectochilus roxburghii, and Leymus chinensis [50][51][52], and light deficiency also weakened the resistance of M. sinostellata [53], stress response TFs were identified and analyzed in a genome wide range. TIFY and mitochondrial transcription termination factors (mTERFs) are related to stress response and have important roles in stress tolerance in plants [72,73].…”
Section: Light Deficiency Affected Stress-related Transcription Factors In M Sinostellatamentioning
confidence: 99%
See 1 more Smart Citation
“…Given that low light intensity can impact stress tolerance in various plants, such as Calamus viminalis, Anoectochilus roxburghii, and Leymus chinensis [50][51][52], and light deficiency also weakened the resistance of M. sinostellata [53], stress response TFs were identified and analyzed in a genome wide range. TIFY and mitochondrial transcription termination factors (mTERFs) are related to stress response and have important roles in stress tolerance in plants [72,73].…”
Section: Light Deficiency Affected Stress-related Transcription Factors In M Sinostellatamentioning
confidence: 99%
“…JA interacts with ethylene signaling pathways to regulate abiotic stress tolerance and may act as a core signal in such an intertwined network [49]. Various studies found that light deficiency can alter stress tolerance and disease resistance in plants [50][51][52][53][54][55][56]. However, its molecular mechanisms in plants are complex and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Under drought and other stress conditions, plants accumulate large amounts of various osmo-protectants such as glycine betaine, proline, soluble sugars, and free amino acids that ultimately maintained the tissue water status and protect the cellular organelles as well as organic molecules from ROS by acting as physical barrier (Farooq et al, 2009;Kumar et al, 2012;Zong et al, 2018). Increased accumulation of osmo-protectants under drought stress might have aggravated stress severity.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf electrical conductance (EC) was measured by adopting Jin-huan et al (2015) method. Soluble sugars content was assayed by anthronecolorimetric method (Zong et al, 2018). The material was put into a centrifuge tube, where 80% ethanol was added.…”
Section: Physiological and Biochemical Attributesmentioning
confidence: 99%
See 1 more Smart Citation